Improvement of methacrylate-based polymer networks by introduction of catechol moieties. (2022) - Fu, D; Szczepanski, CR
Abstract : Purpose/Aim: Dental adhesives mainly consist of methacrylate-based monomers as well as solvents and initiators. The bonding mechanism is based on the penetration of adhesive resins into the demineralized dentin surface and formation of interlocking with exposed collagen fibrils. However, phase separation into hydrophilic/hydrophobic domains leads to water sorption and deterioration of mechanical properties. Furthermore, the esterases and matrix metalloproteinases (MMPs) present in oral environment contribute to methacrylate hydrolysis and collagen degradation, respectively. All these factors accelerate decay along the adhesive interface and cause sub-optimal longevity of the resin filling. A bio-inspired moiety, catechol, has been found to form strong bidentate hydrogen bonds with a variety of surfaces. The purpose of the present study was to design a novel bio-inspired adhesive with catechol moieties and evaluate whether catechol can reduce the heterogeneity of methacrylate-based network structure, decrease water sorption, inhibit the enzyme activities, and improve the longevity of adhesive materials. Materials and Methods: Catechol methacrylate was synthesized by Steglich esterification which is described in the previous literature. The control adhesive formulations include urethane dimethacrylate (UDMA) as crosslinker (50 wt%), 2-hydroxyethyl methacrylate (HEMA) as monomer (50 wt%), and additional 0.5 wt% 2, 2-Dimethoxy-2-phenylacetophenone (DMPA) as photoinitiator. In the novel catechol-contained adhesive, 25 wt% of the HEMA was replaced by catechol methacrylate, with the other components unchanged. To evaluate the performance of these two formulations, dynamic mechanical analysis (DMA), Fourier-transform infrared spectroscopy (FT-IR), water sorption and enzyme (esterases) degradation were conducted to characterize the performance. Results: The novel catechol-contained adhesive showed similar photopolymerization kinetics (final conversion and maximum polymerization rate) to the control one, although multiple works showed that catechol exerts an inhibitory effect on the radial photopolymerization. The water sorption of the novel adhesive, however, was nearly 50% lower than the control adhesive. Moreover, the catechol-contained adhesive showed a higher resistance of the esterase hydrolysis, with less weight loss and lower release of 2-hydroxyethyl methacrylate (HEMA) and methacrylic acid (MMA). Conclusions: The addition of catechol to adhesive formulations reduces the water sorption and improves the resistance of enzyme degradation of methacrylate. These might contribute to the formation of extra hydrogen bonding of catechol in the low-density domains and the inhibitory behaviors of catechol to esterases. Introducing catechol into dental adhesive formulations provides a promising way to enhance the long-term performance of dental adhesive materials. Cytotoxicity and micro-tensile bonding strength tests are essential for the future works.